Influences of proppant on fracture making ability and fracture conductivity in coalbed methane. Issue 3 (August 2019) - Sun, Bin; Guo, Zixi; Zhang, Yi; Zhen, Huaibin; Zhang, Shuling; Zeng, Qinggang
Abstract: The fracture conductivity is one of the most important factors affecting coalbed methane production. The size of proppant, the number of proppant placement layers and the embedment all affect the permeability, thus affecting the fracture conductivity. However, exist research ignored the influence of fracture width. Therefore, according to the formula for calculating the fracture width of acid fracturing, the formula for calculating the fracture width is deduced. According to Carman-Kozeny formula, the fracture conductivity calculation models with and without embedment are respectively established. Through conducting the flow experiment on the coal core, the influence of the number of placement layers and embedment degree on the fracture conductivity is analyzed. The results show that the larger the particle size of proppant is, the more layers are laid, and the wider the fracture width is, thus the greater the fracture conductivity is. The smaller the embedment degree of proppant, the greater the fracture conductivity.